2015
DOI: 10.1063/1.4927651
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent ambipolar carrier injection of electrons and holes with Au electrodes in air-stable field effect transistors

Abstract: Carrier injection from Au electrodes to organic thin-film active layers can be greatly improved for both electrons and holes by nano-structural surface control of organic semiconducting thin films using long-chain aliphatic molecules on a SiO2 gate insulator. In this paper, we demonstrate a stark contrast for a 2,5-bis(4-biphenylyl)bithiophene (BP2T) active semiconducting layer grown on a modified SiO2 dielectric gate insulator between two different modifications of tetratetracontane and poly(methyl methacryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The third is the modulation of gap states at the metal–semiconductor interface, which leads to efficient carrier injection from the electrode to the semiconductor. 69 Therefore, TTC and its analogous small molecules and polymers form a favorable passivation layer, because of its low dielectric constant that reduces polarization effects in the dielectric surface and its high surface energy that leads to a more crystalline film growth of semiconductors. 61 Since ambipolar transistor properties considerably depend on these conditions, surface treatments, passivation layers, and electrode materials are described in Table 1 for individual cases.…”
Section: Energy Levels and Passivation Layersmentioning
confidence: 99%
“…The third is the modulation of gap states at the metal–semiconductor interface, which leads to efficient carrier injection from the electrode to the semiconductor. 69 Therefore, TTC and its analogous small molecules and polymers form a favorable passivation layer, because of its low dielectric constant that reduces polarization effects in the dielectric surface and its high surface energy that leads to a more crystalline film growth of semiconductors. 61 Since ambipolar transistor properties considerably depend on these conditions, surface treatments, passivation layers, and electrode materials are described in Table 1 for individual cases.…”
Section: Energy Levels and Passivation Layersmentioning
confidence: 99%
“…One approach to fabricate ambipolar organic transistor is to investigate and synthesize single‐component electron‐donor and acceptor conjugated molecules (D–A‐conjugated molecules) with tunable energy band alignments, enhanced π‐conjugation and reduced inter‐ring torsions by using appropriate donor (determine HOMO level) and acceptor (dominate LUMO energy) units . The electron withdrawing property resulted from introduced radicals (cyano group and fluorine) and extended conjugation length and augmented intermolecular π–π stacking caused by some inserted organic functional groups in D–A molecules both can contribute to the ambipolar charge injection …”
Section: Ambipolar Organic Semiconducting Materialsmentioning
confidence: 99%
“…In the former, the high density of states inside the gap play an important role for pinning, giving the Bardeen limit 28 . As for the possible conversion from the Schottky to the Bardeen limit, we previously reported that a large vacuum level shift can occur at the MS interface, when the surface texture of pc-OSC is controlled by TTC, which is consistent for the Fermi level pinning associated with DIGS/MIGS 4 . In addition, CDS capture carriers regardless of their polarity and then release them into transporting channels as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 55%
“…Therefore, a thin-film FET of pc-OSC with Au electrodes was fabricated to confirm an equivalent ambipolar performance, which indicates a high purity of pc-OSC material. First, a TTC (9 nm) thin film was deposited on SiO 2 /p ++ -Si substrate, which was cleaned by ultrasonication in acetone, ethanol, and 2-propanol followed by O 2 -prasma treatment, followed by thin-film growth of pc-OSC (30 nm) and finally deposited Au source and drain electrodes with a thermal vacuum evaporator 4 . Purification of pc-OSC and fabrication of an FET were repeated until the FET gives an equivalent ambipolar injection.…”
Section: Methodsmentioning
confidence: 99%